Variability of the preC/C region of hepatitis B virus genotype A from a South African cohort predominantly infected with HIV. Issue 11 (7th August 2013) - Mayaphi, Simnikiwe H.; Martin, Desmond J.; Mphahlele, M. Jeffrey; Blackard, Jason T.; Bowyer, Sheila M.
Abstract Hepatitis B virus (HBV) is a serious global health problem, and HBV genotype is an important determinant of disease progression and treatment outcome. The aim of this study was to assess variations of the precore/core (preC/C) region in HBV genotype A. Sequencing of the preC/C and surface (S) genes of HBV was performed on plasma samples from 20 HBV/HIV co‐infected and 5 HBV mono‐infected individuals. All preC/C study sequences clustered with subgenotype A1, except for two which clustered with subgenotype D4 reference strains. The nucleotide and amino acid variability was far higher in the preC/C region than in the S region. Mutations associated with reduction or failure of HBV e‐antigen (HBeAg) production were observed, with a preC start codon mutation being common (24%). Other mutations (e.g., P5H/L and I97L) associated with severe liver disease were also noticed, some of which were located in the major histocompatibility restricted sites. PreC/C intergenotype nucleotide divergence was >7%, while subgenotypes differed by 2.5–7%. Several study sequences were highly divergent from other African subgenotype A1 strains. This study showed that HBeAg‐negative chronic hepatitis B is underestimated in subgenotype A1, and also highlighted the variant South African A1 strains. The major advantage of preC/C sequencing is that it informs patient management as HBeAg‐negative chronic hepatitis B responds poorly to conventional interferon‐α therapy, and some guidelines treat HBeAg‐negative chronic hepatitis B differently from HBeAg‐positive chronic hepatitis B. These data suggest that subgenotype A1 may be more involved in severe HBV‐related diseases. J Med. Virol. 85:1883–1892, 2013. © 2013 Wiley Periodicals, Inc.